2002
DOI: 10.1143/jjap.41.6867
|View full text |Cite
|
Sign up to set email alerts
|

Epitaxial Growth of SrRuO3Thin Film Electrode on Si by Pulsed Laser Deposition

Abstract: Pseudocubic SrRuO 3 (100) epitaxial thin films were fabricated on Si (100) with a SrO buffer layer by pulsed laser deposition (PLD). Reflection high-energy electron diffraction (RHEED) revealed that the SrO layer is epitaxially grown on naturally oxidized Si substrates with an orientation relationship of SrO (110)/Si (100) and SrO 001 //Si 011 . Subsequent SrRuO 3 deposition resulted in a (100) epitaxial thin film possessing good crystallinity with a full-width at half maximum (FWHM) of 1.9 • in the SrRuO 3 (2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 23 publications
0
5
0
Order By: Relevance
“…TEM analysis has revealed a 6 nm-thick SrO lm on top of amorphous Si-oxide layer, with orientation SrO (110)kSi (100) and SrO h001ikSi h011i. 39 Noteworthy, the stability of this pattern is thickness dependent: 50 nm thick SrO on Si was grown in "cube-on-cube" manner i.e. In the case of our samples, the layer structure observed by TEM is the same for all three routes, with main difference in their thickness.…”
Section: Analysis Of Rheed Patternsmentioning
confidence: 80%
See 3 more Smart Citations
“…TEM analysis has revealed a 6 nm-thick SrO lm on top of amorphous Si-oxide layer, with orientation SrO (110)kSi (100) and SrO h001ikSi h011i. 39 Noteworthy, the stability of this pattern is thickness dependent: 50 nm thick SrO on Si was grown in "cube-on-cube" manner i.e. In the case of our samples, the layer structure observed by TEM is the same for all three routes, with main difference in their thickness.…”
Section: Analysis Of Rheed Patternsmentioning
confidence: 80%
“…57 In Chen et al and Higuchi et al studies the SrO has been used both as buffer layer and deoxidizing agent. 39,58,59 It was observed that during heating of thin SrO layer on Si/SiO 2 a characteristic RHEED pattern is formed, however, only at certain temperature ($700 C). TEM analysis has revealed a 6 nm-thick SrO lm on top of amorphous Si-oxide layer, with orientation SrO (110)kSi (100) and SrO h001ikSi h011i.…”
Section: Analysis Of Rheed Patternsmentioning
confidence: 99%
See 2 more Smart Citations
“…A dc bias voltage was applied to the device through external bias tees in order to protect the network analyzer. orientation may be promoted as a consequence of the structural match between SrO and the Si substrate with a small misfit of −5.5% along the SrO <010>//Si <010> in SrO (100)//Si (100) [11]. As the oxygen pressure was decreased from 1×10 −5 to 6×10 −6 Torr, the intensities of the SrO (200) diffraction peaks slightly increased.…”
Section: Methodsmentioning
confidence: 99%